Formy wsparcia finansowego dla obszarów wiejskich i mieszkańców wsi na przykładzie wybranych gmin Podkarpacia - Sowa, Bożena (MITEL, 2004)
Rozwój obszarów wiejskich wymaga wsparcia finansowego i jest najwyższym priorytetem w polityce gospodarczej kraju. Wsparcie ze środków publicznych umożliwia rozwój wspomnianych obszarów i poprawę warunków życia ich mieszkańców. Szczególną uwagę należy zwrócić na infrastrukturę techniczną, edukacyjną i kulturalną.

The development of rural areas requires financial backing and is of highest priority in a country’s economic policy. The support with public sources makes it possible for the mentioned areas to develop and their people to improve their living conditions. Particular attention should be paid to technical, educational and cultural infrastructure.
Ways of Providing Financial Support to Rural Areas and their Residents on the Basis of the Chosen Communes of the Podkarpacie Region